Poland and the Czech Republic in the Process of Globalization - Elżbieta Kacperska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The purpose of an article was to analyses complexity of the globalization process and its effects for the functioning of the Polish and Czech economies. In addition to the opportunities and threats of the globalization process, the study includes an analysis of the primary indicators for both economies, i.e. GDP, participation in foreign trade, flow of foreign investment and ranking of the KOF globalization index.